KAJIAN HIDROLOGI DAN ANALISA KAPASITAS TAMPANG SUNGAI KRUENG LANGSA BERBASIS HEC-HMS DAN HEC-RAS - Ichsan Syahputra (Jurnal Teknik Sipil Unaya, 2015)
Krueng Langsa  is a river crossing Langsa City the position is in the middle of residential and potentially catastrophic spills seasonal flooding. Krueng Langsa River watershed has an area of 126 km2, with a rainfall of 2300 mm / year and includes areas with relatively high rainfall. In the upper part of the river flow characteristics along the hills, while the central part of the narrowing of the river in the extreme. Hydrologic simulation based on rainfall data using HEC-HMS software obtained flood discharge of 59.30 m³ / sec. Passing the analysis of flood discharge capacity obtained on existing cross-section of 60.07 m³ / sec which is almost close to the value of the existing flood discharge based on the model HEC-HMS. HEC-RAS analysis results with simulation input Q2 years, to 140 pieces of the cross section illustrates that almost all river basins experienced flooding conditions (overflow), and only a few parts that are not experiencing flooding conditions. This is because the flood water level exceeds the elevation of the bank. Scenario flood control is done by normalizing the river, which enlarge the dimensions of the existing river with a wide cross-section of the river on average 20 m to 60 m and planning at the river levee embankment crest elevation +2.00 m and surveillance (freeboard) 0.50 m of surface water flooding . At the mouth of the river, starting from the point STA.0 + 000 to STA.2+ 000  planned use of the river revetment rock pile (Dump Stone). Both scenarios flood control can be recommended to reduce the flooding that occurred in the Krueng Langsa river.